Pengaruh Penerapan Model Pembelajaran Connecting Organizing Reflecting Extending Terhadap Pemahaman Konsep Matematika Peserta Didik Kelas VIII SMPN 13 Padang - RISA MELSI BONI (Departemen Matematika, 2019)
Oneeof the1cognitiveeabilitiessthat is expectedtto be possesseddby every students in learning mathematics is the understanding of mathematical concepts. However, the fact is understanding of mathematical concepts ofiistudents in grade VIII3SMPN 13 Padang is still low, so it needs to be improved. One of the learning models to improve the understanding of mathematical concepts of students is the CORE learning8model. The type of this research are the combination of quasy-experiment and descriptive research with theiiStatic Group Design. Based3on data analysis the0resultrofoquiz it can be conclude that the understanding of mathematicalcconcepts among using CORE model tendencyiiincreasing. Based on the resultsiiof data analysis using t test, it can be concluded that theuunderstanding of mathematical concepts of students that study by1CORE learning modellis better than understanding of mathematical concepts of students that study by direct learning. Keywords – CORE iiLearningiiModel,iiUnderstandingiiof MathematicaliiConcept, Direct learning.